Subjective norms matter for physical activity intentions more than previously thought: Reconsidering measurement and analytical approaches. (July 2019) - Kim, Jeemin; Eys, Mark; Robertson-Wilson, Jennifer; Dunn, Emily; Rellinger, Kayla
Abstract: Objectives: Existing literature consistently demonstrates that subjective norms within the Theory of Planned Behavior (TPB) are a weak predictor of physical activity (PA) intentions, which contradicts humans' innate need to relate to others. A potential explanation relates to methodological shortcomings. Previous studies often ignored individuals' salient normative referents (e.g., parents, friends) and the proposed sub-components of subjective norms: normative belief ( NB ) and motivation to comply (MC) with the pressures. The purpose of this study was to reassess the relationship between subjective norms and PA intentions by addressing these shortcomings. Design: Online surveys were administered at baseline ( N  = 535) and two-weeks post-baseline ( N  = 340). Method: Salient normative referents were elicited with each participant, and NB and MC were assessed in relation to the individually elicited normative referents. Response surface analyses were used to examine the interaction of NB and MC in predicting PA intentions . Results: NB and MC interacted in a complex manner predicting PA intentions. Intentions were higher when NB and MC were both high or both low, and when NB was high and MC was low. The results varied across normative referents. Conclusions: The current results suggest that the weak support for subjective norms found in previous studies may be a function of overlooking individuals' salient normative referents and their willingness to comply with the normative pressures. Highlights: The study assessed subjective norms in relation to physical activity intentions. Salient normative belief (NB) and motivation to comply (MC) were assessed ( N  = 535). Response surface analysis revealed complex interactions of the two factors. Intentions were higher when NB and MC were both high or both low. Current findings offer explanations to previous weak support for subjective norms.